Why vary what’s working? Phase variation and biofilm formation in Francisella tularensis - Mlynek, Kevin D.; Bozue, Joel A. (Frontiers in Microbiology, 2022)
The notoriety of high consequence human pathogens has increased in recent years and, rightfully, research efforts have focused on understanding host-pathogen interactions. Francisella tularensis has been detected in an impressively broad range of vertebrate hosts as well as numerous arthropod vectors and single-celled organisms. Two clinically important subspecies, F. tularensis subsp. tularensis (Type A) and F. tularensis subsp. holarctica (Type B) are responsible for the majority of tularemia cases in humans. The success of this bacterium in mammalian hosts can be at least partly attributed to a unique LPS molecule that allows the bacterium to avoid detection by the host immune system. Curiously, phase variation of the O-antigen incorporated into LPS has been documented in these subspecies of F. tularensis, and these variants often display some level of attenuation in infection models. While the role of phase variation in F. tularensis biology is unclear, it has been suggested that this phenomenon can aid in environmental survival and persistence. Biofilms have been established as the predominant lifestyle of many bacteria in the environment, though, it was previously thought that Type A and B isolates of F. tularensis typically forms poor biofilms. Recent studies question this ideology as it was shown that alteration of the O-antigen allows robust biofilm formation in both Type A and B isolates. This review aims to explore the link between phase variation of the O-antigen, biofilm formation, and environmental persistence with an emphasis on clinically relevant subspecies.